The Dryopteris patula complex (Dryopteridaceae) in Mexico: Morphpmetric analyses - Hernandez-Hernandez, V.=700 1 Terrazas, T.; Delgadillo Moya, C.
(Es, En)
Ilus., ref.
Keywords: HELECHOS; DRYOPTERIS; TAXONOMIA; MEXICO; DRYOPTERIS CINNAMOMEA; FENOGRAMA; SOCIEDAD BOTANICA DE MEXICO